Detail in contemporary bar and restaurant design - Plunkett, Drew.; Reid, Olga. (London, United Kingdom : Laurence King Publishing Ltd., 2013)
Bars and restaurants need to be assertive. Customers tend not to visit them to satisfy basic appetites for food or drink but for the social opportunities. Their interiors need to occupy the imagination of their customers and to whet the appetite for a return visit. The design that gets the formula right will do as much to prolong the life of the business as the products on offer. As this book demonstrates, the conventions and mechanics of eating and drinking influence how bars and restaurants are conceived in different regions of the world. Whatever the final result users are in sustained, intimate contact with the elements of the space they inhabit and detailing must be refined enough, and visually rich enough, to withstand prolonged scrutiny. This book includes a wide range of international projects and for each one there is a descriptive text, colour photographs, floor plans, sections and construction and decorative details. A bonus CD-ROM contains all the drawings as printed in the book, in both EPS and DWG (generic CAD) formats.
Introduction -- Bars and cafes -- Restaurants.
Keywords: BARS (DRINKING ESTABLISHMENTS) -- DECORATION